KONDISI AGRIBISNIS JAGUNG DI KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Ramadhan, Fajri; Hidayati, Filya; Bastoni, Al (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This research aims to determine the fulfillment of corn as feed for poultry (broilers and layers) in Limapuluh Kota Regency, especially in Guguak District as a corn production center in Limapuluh Kota Regency. This study uses a qualitative method. The primary and secondary data obtained were analyzed descriptively. The research is limited to all corn farmers who supply corn for animal feed in Limapuluh Kota Regency. Samples were obtained from all corn farmers who supply corn for animal feed in Guguak District, Limapuluh Kota Regency who have a farming area of >1.0 ha. This research concludes that the implementation of the corn agribusiness system in Guguak District, Limapuluh Kota Regency applies all existing agribusiness subsystems, namely the upstream subsystem (providing production facilities), downstream subsystem (marketing), supporting facilities subsystem and supporting services subsystem.